Implementation of safety performance using safety culture in the oil and gas industry during Covid-19 pandemic / Shawal Sahid Hamid @ Hussain ... [et al.] - Hamid @ Hussain, Shawal Sahid; Mohd Ariff, Anuary Sham; Anuary Sham, Amyra Syafiqah; Jasni, Masliyani Nasuh (Universiti Teknologi MARA, 2022)
The oil and gas industry includes the global processes of exploration, extraction, refining, transporting, and marketing of petroleum products as it becomes central to the economic growth of Malaysia because of its contribution to the fifth of Malaysia's GDP over the past 10 years. However, the emergence of a pandemic that Covid-19 caused the operating environment of the oil and gas industry to experience a monumental shift and subsequently affected workers in the oil and gas industry. As a result, great care and focus are given to the importance of safety culture implementation. The focus of this research is to investigate the influence of safety culture's elements on employee engagement in safety over safety performance, as well as analyze the relationship between safety culture's employee communication and safety performance during Covid-19 among employees at Solar Gas Sdn. Bhd. Furthermore, this study aims to predict safety performance by utilizing the safety culture of employers' leadership in that organization. As part of this questionnaire research, a random sample of 48 Solar Gas Sdn Bhd employees were chosen as respondents. Based on the discussion, discovered that Safety Training is strongly associated with employee safety involvement. However, there is no significant relationship between employee communication and safety training, just as there is no relationship between safety performance and the element of Employers' Leadership in regard to safety culture. In a nutshell, studies show that the employees of the organization do not fully understand and practice the safety culture during this covid 19 pandemic. This makes the safety culture difficult to practice and will indirectly lead to several accidents and the spread of epidemics in the workplace.